Long-Run Career Outcomes of Multiple Job Holding - Johanna Muffert; Regina T. Riphahn (Institute of Labor Economics (IZA), 2025)
Multiple job holding (MJH) is increasingly frequent in industrialized countries. Individuals holding a secondary job add to their experience, skills, and networks. We study the long-run labor market outcomes after MJH and investigate whether career effects can be validated. We employ high-quality administrative data from Germany. Our doubly robust estimation method combines entropy balancing with fixed effects difference-in-differences regressions. We find that income from primary employment declines after MJH spells and overall annual earnings from all jobs increase briefly. Job mobility increases after MJH spells. Interestingly, the beneficial long-term effects of MJH are largest for disadvantaged groups in the labor market such as females, those with low earnings, and low education. Overall, we find only limited benefits of MJH.
Keywords: J22; J24; C21; M53; 330; secondary job holding; moonlighting; Minijob; entropy balancing; investment motive; administrative data; fixed effects; difference-in-differences